The Impact of Family Gender Structure on Financial Asset Micro-investment Decisions : An Analysis of Urban-Rural Differences in the Context of Population-Level Gender Imbalance of Chinese Households (2011 - 2019) - Xiong, Haiyang; Burlakov, Georgi; Mach, Petr, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
This paper explores the impact of female family demographic structures on household asset allocation in the context of China's gender ratio imbalance, with a focus on how demographic changes affect economic decision-making within families. As the disparity between the number of males and females continues to widen, this gender imbalance presents unique challenges and opportunities for the Chinese marriage market and family dynamics. Utilizing data from the China Family Panel Studies (CFPS) from 2012 to 2020, this study analyzes the effect of gender composition on family asset strategies. The findings indicate that the presence of female minors and adults in families negatively impacts the overall level of household and financial assets. The study also finds that in regions with high gender imbalances, these effects are mitigated, revealing a lessened negative relationship between female composition in families and household asset allocation.
Vedoucí práce: Georgi Burlakov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses